Synthesis and Characterization of Mn–C–Codoped TiO2 Nanoparticles and Photocatalytic Degradation of Methyl Orange Dye under Sunlight Irradiation - Wei Xin; Duanwei Zhu; Guanglong Liu; Yumei Hua; Wenbing Zhou (International Journal of Photoenergy)
Novel visible-light-active Mn–C–TiO2 nanoparticles were synthesized by modified sol-gel method based on the self-assembly technique using polyoxyethylenes orbitan monooleate (Tween 80) as template and carbon precursor and manganese acetate as manganese precursor. The samples were characterized by XRD, FTIR, UV-vis diffuse reflectance, XPS, and laser particle size analysis. The XRD results showed that Mn–C–TiO2 sample exhibited anatase phase and no other crystal phase was identified. High specific surface area, small crystallite size, and small particle size distribution could be obtained by manganese and carbon codoped and Mn–C–TiO2 exhibited greater red shift in absorption edge of samples in visible region than that of C–TiO2 and pure TiO2. The photocatalytic activity of synthesized catalyst was evaluated by photocatalytic oxidation of methyl orange (MO) solution under the sunlight irradiation. The results showed that Mn–C–TiO2 nanoparticles have higher activity than other samples under sunlight, which could be attributed to the high specific surface area, smaller particle size, and lower band gap energy.